A Qualitative Case Study in Korean Language Learning Motivations of Filipino Hallyu Fans - Lance Isaac D. Leon; Adrienne Clarisse Caugma; Jeconiah Dreisbach (Development in Language Studies, 2025)
This qualitative study explores the influence of Hallyu, or South Korean popular culture, on the indirect acquisition of the Korean language among Filipino fans. Through a focus group discussion, the study examines participants’ motivations, learning behaviors, and perceptions of Korean language acquisition through media consumption. Findings reveal that repeated exposure to Korean dramas, K-pop, and other cultural products facilitates passive learning, enabling participants to recognize vocabulary, sentence structures, and pronunciation patterns. While some learners actively pursue formal instruction, most rely on informal methods such as peer discussions, digital resources, and incidental exposure. The study also highlights the role of social interactions and personal motivations in sustaining interest in language learning. While participants acknowledge their familiarity with Korean, most do not consider their skills sufficient for practical communication. The study suggests that integrating engaging media-based learning strategies into formal education could enhance language acquisition among young Korean language learners. Future research should explore long-term learning outcomes and intercultural influences of Hallyu in the Philippines.